Test of economic growth and unemployment using vector auto regression in Iraq - Munaf Marza Neama, Sundus Jasim Shaaibith, Shatha Salem Daly (Opción, 2020)
Economic growth and unemployment are considered the most imperative variable for the studies related to construct and implementing economic policies. Hence the core purpose of this study is to examine the cause and effect relationship between two variables “economic growth and unemployment” in Iraq. The time series data has been taken from 1999-2017 and VAR model has been used to test the relationship. Statistical software Eviews 9 has been used to run the VAR model. The results have shown that there is a negative relationship between unemployment and growth rate in Iraq which is economically and statistically significant.